If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 3 = -3(2y + 3) Reorder the terms: 3 + -3y = -3(2y + 3) Reorder the terms: 3 + -3y = -3(3 + 2y) 3 + -3y = (3 * -3 + 2y * -3) 3 + -3y = (-9 + -6y) Solving 3 + -3y = -9 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 3 + -3y + 6y = -9 + -6y + 6y Combine like terms: -3y + 6y = 3y 3 + 3y = -9 + -6y + 6y Combine like terms: -6y + 6y = 0 3 + 3y = -9 + 0 3 + 3y = -9 Add '-3' to each side of the equation. 3 + -3 + 3y = -9 + -3 Combine like terms: 3 + -3 = 0 0 + 3y = -9 + -3 3y = -9 + -3 Combine like terms: -9 + -3 = -12 3y = -12 Divide each side by '3'. y = -4 Simplifying y = -4
| -0.25x+0.5=5 | | 10x=210000 | | 7-14*-12-8+-4=35 | | 75-4x=11-9x | | 6x+3=-6+3x+24 | | 3p^2=-11p-6 | | 8-6x-5-4x=5 | | -4x+12=16 | | 4(3y-5)14y= | | 1/2X+15=37 | | 345*1= | | 7x+3y=85 | | 4w-36=0 | | 15=4x-4 | | 345*233= | | -5+1/4(24n-36) | | x/4+7=-5 | | 2*(-a-8)-15=9 | | 2/I+5 | | 7m-4m= | | 11x-10=12x-49 | | x^3-3x^2+2x+5=0 | | 2x+18=6x+38 | | 2y+3/15=y-1/21 | | (x^3)(x^7)= | | -5x+5/3=7/3 | | I/6-19=-8 | | 13x-7=5+10x | | X/x=1.07 | | 3x+41-5x=1-7x+5 | | A-(17)=-30 | | 8(1-x)-3(7+x)= |